“Writing for English-medium publication is a journey to nowhere — no route and no tools”: Russian academics’ perceptions of the existing publication support; Higher Education; Vol. 89, iss. 6 - Anikina Zh. S. Zhanna Sergeevna (2025, 2025)
Publishing research in English-medium international journals has become highly valued in various academic contexts. The Russian academic context is part of this trend, which puts new pressures on Russian academics. Although a range of measures has been undertaken as publication support, Russian academics’ ability to produce high-quality papers for English-medium international journals remains low. In this paper, we present a study conducted to gain a better understanding of the possible reasons for this phenomenon. It draws on documentary sources produced by 139 academics working at 26 Russian universities. The findings of the study indicate that a large number of Russian academics remain under-represented; the existing publication support is still not focusing appropriately on publishing in English-medium international journals, and is insufficiently diverse to satisfy Russian academics’ individual needs. We conclude by suggesting that wider audiences of Russian academics should be engaged in publication efforts; higher education policymakers and institutional leaders should reconsider the role that higher education institutions play in preparing academics for publishing in English-medium international journals; publication support should focus appropriately on publishing in these journals. This paper will make a useful contribution to the literature by providing fresh insights into the issues experienced by Russian academics along their publication path and determining the areas that need to be addressed. In particular, this may be useful for academics from post-Soviet countries since many of them share common research traditions. However, potential beneficiaries are not limited to them